Beyond Supervision: The Role of Supervisory Support in Improving Work-Life Balance Among Employees of Company X - Paramita Purwanto; Matari Punta Rasikhah (Syntax Literate, 2026)
The development of modern work patterns, characterized by expanded digital connectivity, has led to increased work intensity and job demands. This situation is also experienced by a company in Indonesia’s energy sector. The growing demands in the work domain need to be effectively managed to ensure that employees’ personal life domains are not neglected, and vice versa. However, employee engagement measurement at Company X indicates that work-life balance received the lowest score among key indicators, making it a critical organizational concern. This study aims to examine the relationship between supervisory support and employees’ work-life balance at Company X. The study used a quantitative correlational research design. The participants where employees of Company X. Data were collected to measure levels of supervisory support and work-life balance, and statistical analysis was conducted to determine the relationship between the two variables. The findings reveal a positive relationship between supervisory support and work-life balance among employees of Company X. Among the dimensions of supervisory support assessed, willingness to listen demonstrated the strongest correlation with work-life balance. Supervisory support plays a significant role in enhancing employees’ work-life balance. Strengthening the quality of supervisor–employee relationships, particularly in terms of active listening and open communication, is therefore an essential strategy to promote a healthier balance between professional and personal life within the organization